Human Related Challenges in Agile Software Development of Government Outsourcing Project - Amaliah Khoirun Nisyak; Khairiyah Rizkiyah; Teguh Raharjo (IAES Indonesia Section, 2020)
In 2019, a government organization in Indonesia has developed several systems that will run in parallel using Agile by utilizing vendor services. Based on internal project reports, there are indications of human-related issues or challenges during the development process of these systems. The case study is one of the critical systems of failed projects in this government organization. In this study, a Systematic Literature Review (SLR) was used to identify human-related challenges or issues that could lead to failure in an ASD project. These issues or challenges were qualitatively validated based on expert judgment from external and internal organizations by interview and questionnaire. The final results of this study were 20 human-related challenges grouped into 5 categories, which were identified as human-related challenges that led to the failure of the ASD project in this case study. Proposed solutions based on best practices are also provided for each challenge or issue by conducting business research methods with open and axial coding. Besides, the comparison of views between vendors and organizations on human-related challenges as well as the implications of this study are also presented at the end, so that readers can get insight into these challenges.